PENGARUH PERBEDAAN PEMBERIAN PAKAN IKAN RUCAH DAN KERANG COKLAT (Mytilopsis adamsi) PADA PERTUMBUHAN KEPITING BAKAU (Scylla paramamosain) - Arfat; Abidin, Zaenal; Priyambodo, Bayu (Journal of Fish Nutrition, 2025)
Mangrove crab is one of the leading export commodities in the fisheries sector which has a fairly high selling price at the farmer level. This commodity has great potential to be cultivated in the Asia-Pacific region. However, mangrove crab production in Indonesia is currently still dominated by wild catches because its cultivation activities have not developed optimally. to determine the effect of feeding trash fish and brown mussels on the growth and survival of Mangrove Crabs (S. paramamosain). This study was conducted for 90 days from December 2024 to March 2025. The research location was in the ponds of Candi Manik Village, Sekotong District, West Lombok Regency, West Nusa Tenggara. The research method used 2 treatments, namely trash fish and brown mussels, each of which was repeated 20 times so that 40 experimental units were obtained according to the number of crabs, the treatments tested were trash fish (R) and brown mussels (K). The research data were analyzed using statistical analysis at a real level of 5%. the analysis used to test the results of the experiment was the t-test. The data tested t is the Specific Growth Rate (SGR) value, absolute weight growth, relative weight growth, and crab molting frequency using the mhen withny test while the survival rate (SR) data is analyzed descriptively. The results of the study showed that the absolute, relative, specific weight growth of crabs, molting frequency and survival given feed using brown mussels were higher than those given feed using trash fish. Feeding brown mussels resulted in better absolute, relative, specific growth, molting frequency and survival compared to feeding trash fish on the growth of mangrove crabs. Water quality measurements were within the normal range for the life of mangrove crabs. Keywords: Trash Fish, Mangrove Crabs, Brown Mussels, Molting, Growth